“PHYTO-PHARMACOLOGY OF MOMORDCA DIOICA: A REVIEW” - Das, Doli R.; Sachan, Anupam Kr.; Shuaib, Mohd.; Imtiyaz, Mohd. (Asian Journal of Pharmaceutical Research and Development, 2016)
Herbal drugs play an important role in health care programs especially in developing countries. Ancient Indian literature incorporates a remarkably broad definition of medicinal plants and considers „all‟ plant parts to be potential sources of medicinal substances. Momordica dioica Roxb. Willd is a perennial, dioceous climbing creeper belonging to family Cucurbitaceae. Its common name is Parora, kakora. It is now found to grow in India, Bangladesh, Srilanka, Myanmar, China, Japan, South East Asia, Polynesia, Tropical Africa, and South America. Its cultivation up to an altitude of 1500 meters in Assam and Garo hills of Meghalaya is reported. Fruit is shortly beaked, obtuse with inner red kernel, densely echinate with soft spines, green and yellow at maturity. Seeds are rounded broadly ellipsoid, slightly compressed, slightly and irregularly corrugated enclosed in red pulp. It mainly contains hederagenin, momordicaursenol, momordicin, momordicafoetid, Cucurbitacins and cucurbitane. Its fruits have diuretic, laxative, hepatoprotective, antivenomous, antihypertensive, anti-inflammatory, antiasthmatic, antipyretic, antileprosy, antidiabetic, and antidepressant properties but also its leaves have antihelminthic, aphrodisiac, antihemorroidal, hepatoprotective, antibronchitic, antipyretic, antiasthmatic, and analgesic properties. Oral administration of 50mL of root juice is advised once a day with empty stomach to beat diabetes. The superficial use of root paste over the whole body is believed to act as a sedative in high fever with delirium.